Tradisi Tahfizhul Qur’an Terhadap Hasil Belajar Siswa Di SMP Islam Mbah Bolong Watugaluh Jombang - Khoirun Nisa' (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2020)
Abstract Memorizing of the Al-Qur’an has basically begun since the appearance of the Qur’anic verse it self. Memorizing of the Al-Qur’an is a great virtue. This is a dream for every true person who always wants to worship to Allah SWT, and this is also for humans who are hoping for worldly and spiritual pleasure so that humans become respected people with perfect respect. SMP Mbah Bolong is a school that implements the program of the Al-Qur’an’s memorizing. This School also applies the 2013 curriculum and full day school. Based on this, researchers were interested in research the school which related to student’s memorizing and student learning outcomes. How big is the significance of the rote learning result. Because is seeing the ability of student who are the good ability in memorizing the Al-Qur’an and ofcourse it is on the basis of their love to the Al-Qur’an. Therefore, researchers conducted the research were related to the learning outcomes they obtained. There were of the process of their memorizing Al-Qur’an on the results of the learning they did. The results of the study which obtained that the tradition of memorizing the Al-Qur’an SMP Mbah Bolong emerged from above through a coercive mechanism. The Tradition in school serves to provide confidence in students on memorizing the Al-Qur’an. The students memorize the Al-Qur’an guided by the Al-Qur’an teacher and the module as a guide for their.